Risk of Hospitalization and Death for COVID‐19 in People with Parkinson's Disease or Parkinsonism. Issue 1 (2nd December 2020) - Vignatelli, Luca; Zenesini, Corrado; Belotti, Laura M.B.; Baldin, Elisa; Bonavina, Giuseppe; Calandra‐Buonaura, Giovanna; Cortelli, Pietro; Descovich, Carlo; Fabbri, Giovanni; Giannini, Giulia; Guarino, Maria; Pantieri, Roberta; et al.
ABSTRACT: Background: The risk of COVID‐19 and related death in people with Parkinson's disease or parkinsonism is uncertain. The aim of the study was to assess the risk of hospitalization for COVID‐19 and death in a cohort of patients with Parkinson's disease or parkinsonism compared with a control population cohort, during the epidemic bout (March–May 2020) in Bologna, northern Italy. Methods: Participants of the ParkLink study with the clinical diagnosis of Parkinson's disease or parkinsonism and people anonymously matched (ratio 1:10) for sex, age, district, and Charlson Index were included. The hospital admission rate for COVID‐19 (February 26–May 31, 2020) and the death rate for any cause were the outcomes of interest. Results: The ParkLink cohort included 696 subjects with Parkinson's disease and 184 with parkinsonism, and the control cohort had 8590 subjects. The 3‐month hospitalization rate for COVID‐19 was 0.6% in Parkinson's disease, 3.3% in parkinsonism, and 0.7% in controls. The adjusted hazard ratio (age, sex, district, Charlson Index) was 0.8 (95% CI, 0.3–2.3, P = 0.74) in Parkinson's disease and 3.3 (1.4–7.6, P = 0.006) in parkinsonism compared with controls. Twenty‐nine of the infected subjects died; 30‐day fatality rate was 35.1%, without difference among the 3 groups. Six of 10 Parkinson's disease/parkinsonism patients had the infection during hospitalization or in a nursing home. Conclusions: Parkinson's disease per se probably is not a risk factor for COVID‐19 hospitalization. Conversely, parkinsonism is an independent risk factor probably because of a more severe health status, entailing higher care dependence and placement in high‐infection‐risk accommodations. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society